A Chemical Controller of SNARE-Driven Membrane Fusion That Primes Vesicles for Ca2+-Triggered Millisecond Exocytosis - Heo, Paul; Yang, Yoosoo; Han, Kyu Young; Kong, Byoungjae; Shin, Jong-Hyeok; Jung, Younghoon; Jeong, Cherlhyun; Shin, Jaeil; Shin, Yeon-Kyun; Ha, Taekjip; Kweon, Dae-Hyuk (AMER CHEMICAL SOC, 2016)
Membrane fusion is mediated by the SNARE complex which is formed through a zippering process. Here, we developed a chemical controller for the progress of membrane fusion. A hemifusion state was arrested by a polyphenol myricetin which binds to the SNARE complex. The arrest of membrane fusion was rescued by an enzyme laccase that removes myricetin from the SNARE complex. The rescued hemifusion state was metastable and long-lived with a decay constant of 39 min. This membrane fusion controller was applied to delineate how Ca2+ stimulates fusion-pore formation in a millisecond time scale. We found, using a single-vesicle fusion assay, that such myricetin-primed vesicles with synaptotagmin 1 respond synchronously to physiological concentrations of Ca2+. When 10 mu M Ca2+ was added to the hemifused vesicles, the majority of vesicles rapidly advanced to fusion pores with a time constant of 16.2 ms. Thus, the results demonstrate that a minimal exocytotic membrane fusion machinery composed of SNAREs and synaptotagmin 1 is capable of driving membrane fusion in a millisecond time scale when a proper vesicle priming is established. The chemical controller of SNARE-driven membrane fusion should serve as a versatile tool for investigating the differential roles of various synaptic proteins in discrete fusion steps.
Keywords: SYNAPTIC VESICLES; SINGLE-MOLECULE; NEUROTRANSMITTER RELEASE; COMPLEX; SYNAPTOTAGMIN; PROTEINS; DYNAMICS; INTERMEDIATE; HEMIFUSION; MACHINERY